Revealing what is distinct by recognising what is common: distinguishing between complex PTSD and Borderline Personality Disorder symptoms using bifactor modelling. Issue 1 (31st December 2020) - Frost, Rachel; Murphy, Jamie; Hyland, Philip; Shevlin, Mark; Ben-Ezra, Menachem; Hansen, Maj; Armour, Cherie; McCarthy, Angela; Cunningham, Twylla; McDonagh, Tracey
ABSTRACT: Background : Despite concerns of conceptual similarity, increasing evidence supports the discriminant validity of Complex Posttraumatic Stress Disorder (CPTSD) and Borderline Personality Disorder (BPD). However, all studies to date have assumed a categorical model of psychopathology. In contrast, dimensional models of psychopathology, such as the Hierarchical Taxonomy of Psychopathology model (i.e. HiTOP model), recognise shared vulnerability across supposedly discrete disorders. Accounting for shared vulnerability between CPTSD and BPD symptoms may help to better reveal what is unique about these constructs. Objective : To identify the distinct and shared features of CPTSD and BPD via the application of dimensional modelling procedures. Method : Confirmatory bifactor and confirmatory factor analysis were employed to identify the optimal latent structure of CPTSD and BPD symptoms amongst a convenience sample of Israeli adults ( N = 617). Additionally, structural equation modelling was used to identify risk factors associated with these constructs. Results : The latent structure of CPTSD and BPD symptoms was best explained by a bifactor model including one 'general' factor (i.e. vulnerability to all symptoms) and three 'specific' correlated factors (i.e. vulnerability to PTSD, DSO, and BPD symptoms, respectively). CPTSD symptoms were more readily distinguished from the general factor whereas BPD symptoms were not as easily distinguished from the general factor. CPTSD symptoms reflecting a negative self-concept and BPD symptoms reflecting an alternating self-concept were the most distinctive features of CPTSD and BPD relative to the general factor, respectively. Most of the risk factors were associated with the general vulnerability factor, consistent with the predictions of dimensional models of psychopathology regarding shared risk across supposedly distinct psychiatric constructs. Conclusion : Consistent with a dimensional model of psychopathology, CPTSD and BPD shared a common latent structure but were still distinguishable. CPTSD and BPD symptoms may be most effectively distinguished based on the phenomenology of self-concept symptoms. Abstract : HIGHLIGHTS: CPTSD and BPD symptoms shared a common latent structure consistent with a dimensional model of psychopathology. Recognition of this shared latent structure afforded the opportunity to highlight the phenomenological signatures which may distinguish CPTSD and BPD. CPTSD was most effectively distinguished by a fixed negative view of the self, whereas BPD was characterised by an alternating sense of self.